Relativistic shifted-l expansion technique for Dirac and Klein-Gordon equations - Mustafa, O; Barakat, T (Iop Publishing Ltd, 1998)
The shifted-l expansion technique (SLET) is extended to solve for Dirac particle trapped in spherically symmetric scalar and/or 4-vector potentials. A parameter lambda = 0, 1 is introduced in such a way that one can obtain the Klein-Gordon (KG) bound states from Dirac bound states. The I-vector Coulomb, the scalar linear, and the equally mixed scalar and 4-vector power-law potentials are used in KG and Dirac equations. Exact numerical results are obtained for the Q-vector Coulomb potential in both KG and Dirac equations. Highly accurate and fast converging results are obtained for the scalar linear and the equally mixed scalar and 4-vector power-law potentials.
Keywords: shifted-l expansion technique